THU0321 Increased Frequency of Hand Osteoarthritis in Patients with Primary Sjogren's Syndrome: Is there a Relationship between Two Diseases?. (23rd January 2014) - Aksoy, A.; Solmaz, D.; Can, G.; Cetin, P.; Balci, A.; Akar, S.; Birlik, M.; Akkoc, N.; Onen, F.
Abstract : Background: The distribution of arthritisin primary SjSis similarto that of rheumatoid arthritis (RA), primarily affecting the small joints of the hands. Unlike RA, erosive arthritis is rarely seen in primary SjS. In daily rheumatology practice, we noticed that hand osteoarthritis (OA), especially erosive hand OA, is commonly associated with primary SjS. In the review of literature, we found no controlled study investigating the relationship between primary SjS and erosive hand OA although there are some published observations similar to ours. Objectives: To investigate the prevalence of hand OA in patients with primary SjS. Methods: The patients with primary SjS followed up in a university hospital were called by telephone and invited to participate to the study. Systemic lupus erythematosus (SLE) patients were included as controls in the study. We obtained a detailed medical history and performed full physical examination in all patients who agreed to take part in the study. Standard hand/wrist X-rays were ordered. They were read by an experienced rheumatologist and a radiologist. They were classified according to the Kellgren-Lawrence (KL) classification system. Results: We included 119 patients (115 female; 4 male) with primary SjS fulfilling the American-European classification criteria for primary SjS in this study. The mean age was 51.6 years. Initial symptoms were as follow: arthralgia (62.3%), dry eye (19.3%) and dry mouth (14.9%). Anti-nuclear antibody (ANA) was found to be positive in 72 patients (66.2%), rheumatoid factor (RF) in 31 patients (32%) and anti-CCP antibody in 3 patients (5.4%). In total, 34 SLE patients were enrolled as controls. Their mean age was 42.4 years. Ninety seven percent of patients had arthralgia and 58% of patients had arthritis. The hand/wrist X-rays were obtained in 114 primary SjS patients (110 female; 4 male) and in 34 (33 female and 1 male) SLE patients. Inter-observer reliability for diagnosing radiographic OA and erosive OA was good (ĸ=0.791 and ĸ=0.578 respectively). Among 114 primary SjS patients, 45 patients (39.4%) had radiographic hand OA, 32 (28.0%) had symptomatic hand OA and 21 (16.1%) had erosive hand OA. Joint involvement pattern similar to that in RA were reported in only two patients. The prevalence of radiographic hand OA (33.3%) and erosive hand OA (11.2%) in 90 primary SjS patients who were age and sex-matched with SLE patients, were significantly higher than those (15.2% and 0 respectively) in SLE patients (p=0.005 and p=0.035, respectively). The frequency of hand OA in primary SjS patients was found to be positively correlated with increasing age (r:0.513, p<0.001). Primary SjS patients with erosive hand OA had significantly higher mean age than those without erosive hand OA (p<0, 001). Cigarette smoking (p<0.05) and ANA positivity (p<0.001) were less common among the patients with erosive hand OA than those without erosive hand OA. Conclusions: This study suggests that the frequency of radiographic and erosive hand OA may be higher in primary SjS patients than expected and confirms our clinical observations. However, it should be taken into consideration that methodological and geographic differences between the studies may affect the results. Disclosure of Interest: None Declared